ANALISIS TEORITIS THERMODINAMIKA PADA TEMPERATUR GAS BUANG MOTOR DIESEL 2500 CC DAN PENGARUHNYA TERHADAP SUDU – SUDU TURBIN TURBO CHARGER - Legisnal Hakim (Universitas Pasir Pengaraian, 2010)
Motor diesel is growing rapidly now, and have a better performance, technology and construction machinery has undergone innovation - innovation that spectacular, fuel system, air intake systems and other systems, which can support the engine performance is also experiencing a very recent innovation. Diesel engines are usually called compression ignition engine (compression ignition engines), how ignition fuel is done by spraying fuel into the air that has been pressurized and high temperature. Currently diesel engine with a small total volume produce big power, is none other than the already wide use of the turbo charger to add the intake air pressure and increase the effective pressure, increased air temperature in the cylinder so the engine power increased by approximately 25% compared to engines without turbo chargers . Turbo Charger driven by exhaust gases from combustion, where the turbo charger has two main components of the turbine wheel, made of heat-resistant cast metal and compressor wheels, made of aluminum alloy in rollers and then done.